Exploring norms indispensable for both emergence and maintenance of cooperation in indirect reciprocity - Yamamoto, Hitoshi; Okada, Isamu; Uchida, Satoshi; Sasaki, Tatsuya (Frontiers in Physics, 2022)
Indirect reciprocity is one of the major mechanisms of the evolution of human cooperation. In indirect reciprocity, social norms with which individuals distinguish the good people from the bad people play essential roles. On the one hand, previous studies have suggested the various different norms which are evolutionarily stable against the invasion of free riders. However, these approaches could not reveal what norms would be selected in the process of evolution of cooperation, because they are based on the premise that a single norm is shared in a society. On the other hand, recent studies have tackled the mechanisms of the co-evolution of norms and cooperation. However, the norms which are necessary for emergence or sustenance of cooperation have not been revealed. Here we show some indispensable norms for emergence and sustenance of cooperation using a norm knockout method which has been developed to analyze a function of each norm in the environment of coexistence of many norms. The results revealed that norms as known as "shunning" and "image scoring" are indispensable in the emergence of cooperation, but they are not required after a cooperative society is achieved. Furthermore, "simple standing" is a unique norm which is necessary to maintain cooperation. We call the former as a pioneer norm and the latter as a keystone norm. The results indicate importance to focus on the dynamics of evolution because the role of indispensable norms has been overlooked by the static analysis of evolutionarily stable norms.